Hubungan Kepatuhan Diet Dan Gaya Hidup Terhadap Kadar Gula Darah Pada Pasien Diabetes Mellitus Type 2 - santosa, winanda rizki bagus; Akasyah, Wildan (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2024)
Introduction: Frequent consumption of foods and drinks containing sugar and unhealthy lifestyles are an emergency problem for type 2 diabetes mellitus patients. In type 2 diabetes mellitus patients, unhealthy lifestyles and irregular diets cause disease complications resulting in frequent deaths. Objective: This study aims to determine the relationship between diet and lifestyle adherence to blood sugar levels in patients with type 2 diabetes mellitus. Method: Correlational research design using a cross-sectional approach. This research was conducted for the period 1 November 2023 - 30 November 2023. The population in this study were patients diagnosed with T2DM at public health centers X and Y, in Kediri City. Sample measurements can use G Power with a power analysis effect size of 0.5, α err prob 0.05, power (0.95), and an increase in sample size of 20% to obtain a sample of 56 respondents. The sample selection technique was purposive sampling based on inclusion criteria, namely that the patient was willing to take part in the research until completion, the patient could read and write, and the patient was diagnosed with T2DM by a doctor at the public health centers X and Y, in Kediri City. The research statistical test used Spearmans Rho. Results: The relationship between diet and blood sugar levels in type 2 diabetes mellitus patients showed that the majority of type 2 diabetes mellitus patients had poor diet patterns and blood sugar levels ≥ 126, namely 64.3%. The results of the analysis of the relationship between diet and blood sugar levels also showed a p-value of 0.001 < 0.05. The relationship between lifestyle and blood sugar levels in T2DM showed that the majority had poor lifestyles and blood sugar levels ≥ 126, namely 67.9%. The results of the analysis of the relationship between lifestyle and blood sugar levels also showed a p-value of 0.000 < 0.05. Conclusion: There is a relationship between diet and lifestyle on blood sugar levels in type 2 diabetes mellitus patients. Suggestion: In T2DM patients, avoid eating foods and snacks that contain high sugar, and high fat, and control portion sizes to manage blood sugar levels. Do regular physical activity, according to your abilities and doctor's recommendations. Walking, cycling, and other sports can be good choices for controlling blood sugar.